Contrasting strategies of hydraulic control in two codominant temperate tree species. Issue 3 (23rd December 2016) - Matheny, Ashley M.; Fiorella, Richard P.; Bohrer, Gil; Poulsen, Christopher J.; Morin, Timothy H.; Wunderlich, Alyssa; Vogel, Christoph S.; Curtis, Peter S.
Abstract: Biophysical controls on plant water status exist at the leaf, stem, and root levels. Therefore, we pose that hydraulic strategy is a combination of traits governing water use at each of these three levels. We studied sap flux, stem water storage, stomatal conductance, photosynthesis, and growth of red oaks ( Quercus rubra ) and red maples ( Acer rubrum ). These species differ in stomatal hydraulic strategy and xylem architecture and may root at different depths. Stable isotope analysis of xylem water was used to identify root water uptake depth. Oaks were shown to access a deeper water source than maples. During non‐limiting soil moisture conditions, transpiration was greater in maples than in oaks. However, during a soil dry down, transpiration and stem water storage decreased by more than 80% and 28% in maples but only by 31% and 1% in oaks. We suggest that the preferential use of deep water by red oaks allows the species to continue transpiration and growth during soil water limitations. In this case, deeper roots may provide a buffer against drought‐induced mortality. Using 14 years of growth data, we show that maple growth correlates with mean annual soil moisture at 30 cm but oak growth does not. The observed responses of oak and maple to drought were not able to be explained by leaf and xylem physiology alone. We employed the Finite‐difference Ecosystem‐scale Tree Crown Hydrodynamics model version 2 plant hydrodynamics model to demonstrate the influence of root, stem, and leaf controls on tree‐level transpiration. We conclude that all three levels of hydraulic traits are required to define hydraulic strategy.